The impact of internet use in the digital era on public political trust in China—An empirical study based on CGSS 2021 data - Yanan Wen; Xue Sun; Lu Fang (PLoS ONE, 2025)
Background The system of the congresses of the Chinese people is the fundamental political system established by the Chinese people under the leadership of the Communist Party of China (CPC), suited to China’s national conditions. As China’s highest national authority organ, the National People’s Congress (NPC) plays an important role in China’s development. The trust of the Chinese public for the NPC objectively reflects the level of trust by the Chinese public and their confidence in the people’s congress system. Methods Based on Chinese general social survey (CGSS) 2021 data and using SPSS22 software, this paper examines the impact of public Internet use on political trust through binary logistic analysis and ordinal regression analysis methods. Results and Conclusions Research showed that the use of the Internet and its use frequency does not affect public’s responsiveness to political trust questions, but the use of the Internet affects the political trust level of the public. People who do not use the Internet at all and those who use the Internet daily are significantly different, and the former hold a higher political trust level than the latter. Moreover, the level of trust of people using the Internet several times per week is markedly lower than that of daily Internet users; no significant differences were found in the level of trust of people using the Internet several times a year or less, several times a month, and daily.